2017
DOI: 10.2337/db17-0321
|View full text |Cite
|
Sign up to set email alerts
|

Clec16a, Nrdp1, and USP8 Form a Ubiquitin-Dependent Tripartite Complex That Regulates β-Cell Mitophagy

Abstract: Mitophagy is a cellular quality-control pathway, which is essential for elimination of unhealthy mitochondria. While mitophagy is critical to pancreatic β-cell function, the posttranslational signals governing β-cell mitochondrial turnover are unknown. Here, we report that ubiquitination is essential for the assembly of a mitophagy regulatory complex, comprised of the E3 ligase Nrdp1, the deubiquitinase enzyme USP8, and Clec16a, a mediator of β-cell mitophagy with unclear function. We discover that the diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 51 publications
6
89
0
Order By: Relevance
“…Studies in mammalian systems also support a role for CLEC16A in the development of T1D. Indeed, we previously identified that CLEC16A maintains insulin secretion and glucose homeostasis by regulating the formation of a ubiquitin-dependent mitophagy complex within pancreatic β cells [7,8,10]. Beyond studies demonstrating a role for CLEC16A SNPs in human β-cell function, we also observed that pharmacological inhibition of the CLEC16Amitophagy pathway impaired β-cell function in humans [10].…”
supporting
confidence: 54%
See 3 more Smart Citations
“…Studies in mammalian systems also support a role for CLEC16A in the development of T1D. Indeed, we previously identified that CLEC16A maintains insulin secretion and glucose homeostasis by regulating the formation of a ubiquitin-dependent mitophagy complex within pancreatic β cells [7,8,10]. Beyond studies demonstrating a role for CLEC16A SNPs in human β-cell function, we also observed that pharmacological inhibition of the CLEC16Amitophagy pathway impaired β-cell function in humans [10].…”
supporting
confidence: 54%
“…1). Formerly known as KIAA0350, CLEC16A regulates mitochondrial autophagy and endosomal maturation [7][8][9][10]. CLEC16A is flanked by two neighboring genes: CIITA, which is required for the expression of MHC Class II, and SOCS1, a negative modulator of cytokine signaling.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CLEC16A plays a role in mitochondrial autophagy (mitophagy), a process to eliminate unhealthy mitochondria that is essential for maintaining beta-cell function, glucose homeostasis and GSIS (glucose-stimulated insulin secretion); inhibition of the CLEC16A-related pathway impairs beta-cell oxygen consumption and insulin secretion (98). A ubiquitin-dependent tripartite composed of CLEC16A, NRDP1, and USP18 was reported to act as a regulator of beta-cell mitophagy (99). A previous study found that pancreas-specific CLEC16A deficiency led to impaired glucose tolerance, ER stress and GSIS in mice, and a SNP in the CLEC16A gene (rs12708716) associated with reduced expression resulted in impaired beta-cell function in humans (98).…”
Section: Clec16amentioning
confidence: 99%